The effect of carprofen administration on conception rate after artificial insemination on heifers with prolonged in breeding age - Fatma Satılmış; Hasan Alkan; Ömer Faruk Yeşilkaya; Muhammed Furkan Çiftçi; Hüseyin Erdem (Eurasian Journal of Veterinary Sciences)
Aim: The aim of this study was to determined the effect of carprofen administration on conception rate after artificial insemination on heifers with prolonged in breeding age Materials and Methods: Animal material of the study formed; at the age of 18 months and over, 156 head Simental and Brown breed heifers with body condition score of 3,50, was'nt obtained pregnancy although it was inseminated >3 times before. PGF2α was administered intramuscularly to heifers in which on rectal palpation and real-time ultrasound examinations, corpus luteum is determined in the ovary and do not detect any pathology in the oviduct, uterus, cervix, vagina and vulva. On the second and third days after prostaglandin F2α administration, artificial insemination was performed on heifers with showing oestrus (day 0). Inseminated heifers were divided into two experimental groups. Carprofen was administered subcutaneously to the heifers in the Karprofen -13 (Kr-13) group on the 13th day and Karprofen -14 (Kr-14) on the 14th day . No administered was made to the heifers the control groups of both experimental groups. Pregnancy examinations of the inseminated heifers were performed on the 30th day by real time ultrasonography Results: Conception rates in the 13th day experimental and control groups were 46,80% and 47,36%, respectively; On the 14th day, it was determined as 37,14% and 47,22% in the experimental and control groups (p> 0,05). Conclusion: As a result, it has been determined that the carprofen administration does not increase the pregnancy rate on the 13th or 14th day after insemination in heifers with prolonged in breeding age.